تقويم برامج الدراسات العليا بجامعة نزوى في ضوء معايير الجودة والاعتماد الأكاديمي - صابرة بنت حمد بن سالم العوفي; Sabirah binti Hamad ibn Salim Al-'Awfi (Universiti Sains Islam Malaysia, 2024)
Matric: 4160047 (FPBU)